Distribution Pattern Presentation Resident with Access to Healthy Toilets 2015-2022 Regency Mappi Papua Province - Nilda Fadila; Der Nayun (Journal of Health Science and Pharmacy, 2025)
Background: A decent or healthy toilet is a sanitation facility designed to prevent the transmission of diseases through human feces. A healthy toilet must be able to safely contain and manage excreta without contaminating the environment, water sources, or soil, and it must prevent direct contact between humans and waste. Toilet use behavior is influenced by internal factors such as age, gender, and level of knowledge. In addition, socio-economic factors including education, attitudes, habits, occupation, income, and ethnicity also play an important role. External factors include the availability of toilet facilities, the cleanliness and hygiene conditions of toilets, and access to clean water. Objective: This study aims to determine the percentage of residents with access to healthy toilets in Mappi Regency, Papua Province, during the period 2015–2022. Method: This study employed a descriptive quantitative approach using secondary data obtained from the Mappi Regency Health Profile. The data analyzed consisted of annual percentages of the population with access to healthy toilets. Data analysis was conducted by compiling information into tables and graphs, followed by narrative interpretation to identify patterns and trends. Results: The findings indicate fluctuations in access to healthy toilets, suggesting ongoing challenges in improving sanitation coverage. The lowest access was recorded in 2018 at 2.72%, while the highest occurred in 2019 at 26.43%. A decline was observed in 2020 to 6.30%, followed by an increase in 2021 and 2022. Conclusion: The distribution of access to healthy toilets in Mappi Regency demonstrates persistent challenges in sanitation improvement. Both internal and external factors influence toilet use behavior. Therefore, community-based interventions, preventive and promotive actions, and evidence-based policies are essential to increase access to healthy toilets and reduce environment-related diseases.